Uncovering the Secret of Diagonal Ear Lobe Crease - Bisoyi, Diptiranjani; Kar, Shiba Ranjan; Nayak, Sudeepta; Das, Smruti Ranjan; Sahoo, Chandan Kumar (Nepal Journal of Dermatology, Venereology & Leprology, 2025)
Frank’s sign is a diagonal crease of the earlobe that runs from the tragus across the lobule to the posterior margin of the auricle. Commonly referred to as the diagonal earlobe crease (DELC), it has been considered a potential marker of diabetes, cardiovascular disease, and other metabolic conditions. Since both the heart and the earlobe are supplied by end arteries, it was once believed that DELC and heart disease might develop concurrently, as collateral circulation is limited when vascular damage occurs. Some studies have also suggested an association with aging and polycystic ovarian syndrome. Early diagnosis is essential in order to provide effective therapy, reduce mortality, and improve quality of life. However, further research is required to better establish the diagnostic significance of Frank’s sign and its clinical applications. Here, we report five cases of DELC with varied associated disorders.